PENGARUH PEMBELAJARAN BERDIFERENSIASI BERBANTUAN MEDIA WORDWALL TERHADAP PENALARAN MATEMATIS SISWA - Erlina, Lisa; Sutikno, M. Sobry; Hidayati, Djuita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of differentiated learning assisted by Wordwall media on the mathematical reasoning abilities of fifth-grade students in Mathematics at MIN 3 Kota Mataram. Differentiated learning was implemented to adapt the learning process to students’ needs, interests, and learning styles so that students could actively engage in learning activities. The use of Wordwall as an interactive learning medium was expected to help students understand mathematical concepts, increase learning activities, and develop mathematical reasoning skills through engaging and varied activities. This study employed a quantitative approach with an experimental research type and a quasi-experimental design in the form of a nonequivalent control group design. The population consisted of all fifth-grade students at MIN 3 Kota Mataram, totaling 88 students. The research sample included Class V B as the experimental class and Class V C as the control class, each consisting of 29 students. Data collection techniques used descriptive test questions to measure mathematical reasoning ability. The research instruments were tested through validity, reliability, discrimination index, and difficulty level analyses. Data analysis was conducted using the Shapiro–Wilk normality test, Levene’s test for homogeneity, and the Independent Samples t-test with the assistance of the JASP application. The results showed that differentiated learning assisted by Wordwall media had a significant effect on students’ mathematical reasoning abilities. This was indicated by the average post-test score of the experimental class, which was 77.069, higher than the control class average of 67.241. The hypothesis test results showed that statistic = 4.947 with a significance value of p < 0.001, meaning that Ha was accepted and Ho was rejected. Therefore, differentiated learning assisted by Wordwall media was more effective than conventional learning in improving students’ mathematical reasoning abilities. In addition, students appeared more active and enthusiastic during the learning process.